REVITALISASI PEMBELAJARAN KITAB KUNING UNTUK PENGUATAN LITERASI KEISLAMAN SANTRI DI PESANTREN - Nadia Nabila; Muhammad Husni (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The aim of this study is to re-examine the learning methods of the kitab kuning as an effort to strengthen Islamic literacy among students in the modern era. This research is based on the need of Islamic boarding schools (pesantren) to preserve the scholarly tradition of turats while adapting to the development of modern education. This study employs a descriptive qualitative approach based on literature review and investigates various references on kitab kuning learning methods, innovations in pesantren education, and the integration of 21st-century competencies. The findings indicate that the revitalization of kitab kuning learning can be achieved through the use of more participatory educational approaches, strengthening the sociocultural context in understanding classical texts, and utilizing digital technology to assist students in interpreting classical literature. A modern curriculum that integrates technological skills, critical thinking abilities, and effective communication competencies can help students gain a deeper understanding while maintaining the scholarly authority and depth characteristic of pesantren. This revitalization demonstrates that kitab kuning remains relevant and continues to meet the needs of contemporary Islamic education. The results support the theory of Islamic education modernization, which emphasizes the importance of innovation while preserving tradition. Pesantren remain relevant Islamic educational institutions amid the dynamics of changing times because the revitalization of kitab kuning learning serves as an essential strategy in shaping moderate, adaptive students with strong Islamic literacy.